Feeding plasticity more than metabolic rate drives the productivity of economically important filter feeders in response to elevated CO2 and reduced salinity. (25th July 2018) - Rastrick, Samuel P S; Collier, Victoria; Graham, Helen; Strohmeier, Tore; Whiteley, Nia M; Strand, Øivind
Abstract: Climate change driven alterations in salinity and carbonate chemistry are predicted to have significant implications particularly for northern costal organisms, including the economically important filter feeders Mytilus edulis and Ciona intestinalis. However, despite a growing number of studies investigating the biological effects of multiple environmental stressors, the combined effects of elevated p CO2 and reduced salinity remain comparatively understudied. Changes in metabolic costs associated with homeostasis and feeding/digestion in response to environmental stressors may reallocate energy from growth and reproduction, affecting performance. Although these energetic trade-offs in response to changes in routine metabolic rates have been well demonstrated fewer studies have investigated how these are affected by changes in feeding plasticity. Consequently, the present study investigated the combined effects of 26 days' exposure to elevated p CO2 (500 µatm and 1000 µatm) and reduced salinity (30, 23, and 16) on the energy available for growth and performance (Scope for Growth) in M. edulis and C. intestinalis, and the role of metabolic rate (oxygen uptake) and feeding plasticity [clearance rate (CR) and absorption efficiency] in this process. In M. edulis exposure to elevated p CO2 resulted in a 50% reduction in Scope for Growth. However, elevated p CO2 had a much greater effect on C. intestinalis, with more than a 70% reduction in Scope for Growth. In M. edulis negative responses to elevated p CO2 are also unlikely be further affected by changes in salinity between 16 and 30. Whereas, under future predicted levels of p CO2 C. intestinalis showed 100% mortality at a salinity of 16, and a >90% decrease in Scope for Growth with reduced biomass at a salinity of 23. Importantly, this work demonstrates energy available for production is more dependent on feeding plasticity, i.e. the ability to regulate CR and absorption efficiency, in response to multiple stressors than on more commonly studied changes in metabolic rates.